Doctor Strange in the multiverse of madness [videorecording (DVD)] - Cumberbatch, Benedict, 1976-; Olsen, Elizabeth, 1989-; Ejiofor, Chiwetel; Wong, Benedict; Gomez, Xochitl; Stuhlbarg, Michael; McAdams, Rachel, 1978-; Elfman, Danny (Marvel Studios, 2022)
Doctor Strange tampers with a risky forbidden spell that alters time and space and accidentally opens a gateway to the multiverse. Together with the Scarlet Witch and the unflappable Wong, Doctor Strange confronts countless dangers in strange and mysterious alternate realities to attempt to restore a single stable reality. As they travel through myriad different layers of the multiverse, they face down a new yet unsettlingly familiar adversary that they will need help to conquer.